Behavior problems of the elementary school children in the Division of Pasay City schools - Uyengco, Priscila P. 1913- (1960)
The author aimed to find out the nature of behavior problems common among the public elementary school children in the Division of City Schools, Pasay City, and the different elements and factors that contribute to the causation and development of these behavior problems.